Robert Pippin, Metaphysical Exile: On J.M. Coetzee’s Jesus Fictions. - Abraham, Ibrahim (Journal for the academic study of religion, 2021)
Robert Pippin, Metaphysical Exile: On J.M. Coetzee’s Jesus Fictions. New York: Oxford University Press, 2021, pp. 137, ISBN: 9780197565940 (hbk). US$74.00.